Work design and team learning: identification of predictive power - Katia Elizabeth Puente-Palacios; Marcela Guimarães Côrtes; Thiago Gomes Nascimento (Revista Psicologia)
Team learning constitutes a subject that has aroused great interest, but the knowledge built up so far still does not clearly answer the questions about its main antecedents. Thus, the objective of this study was to measure the predictive power of work design in relation to team learning. An empirical study was carried out with a sample of 362 individuals organized in 106 teams. The information was collected through the application of questionnaires with previously obtained validity evidence. The results showed that the factors, Characteristics of the tasks and Characteristics of knowledge, two dimensions of work design, have a significant effect (R2 = 17%) on team learning. These results demonstrate that team managers should pay attention to aspects such as autonomy or variety of tasks, as well as to the demands and complexity of knowledge, since these aspects affect to what extent teams adopt learning behavior